LEGAL OVERVIEW OF TRADEMARKS AND GEOGRAPHICAL INDICATIONS - Erisa Ardika Prasada (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This article discusses the importance of trademarks and geographical indications in the business world, especially in the context of marketing, consumer protection, and producer reputation building. Trademarks serve as a marker that distinguishes one producer's goods or services from another, while geographical indications indicate the geographical origin of a good that has a special quality or reputation due to environmental factors. Legal protection of geographical indications aims to prevent misuse of geographical names by unauthorized parties, protect original producers, and preserve culture and traditional knowledge. This research uses normative legal methods to examine the legal principles underlying the importance of regulating trademarks and geographical indications. This research uses a study of primary legal materials from legislation and secondary legal materials from related literature. The results show that legal protection of geographical indications provides significant benefits, including product identification, protection from fraudulent competition, quality assurance, increased production, and preservation of culture and natural beauty. It also plays a role in enhancing the reputation of products and regions, which has a positive impact on local economic development. In addition, this protection not only provides economic benefits to the region, but also provides assurance to consumers about the quality of the product. Therefore, legal protection of geographical indications is a crucial step in maintaining the quality, reputation and sustainability of superior products from various regions in Indonesia.